Solar light responsive photothermal superhydrophobic ice-repellent coating, preparation method thereof and application thereof in power transmission wire
Patent Information
- Application Number
- CN202611331475.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-31
- Publication Date
- 2026-10-30
AI Technical Summary
[0005]本发明的主要目的在于针对现有光热超疏水防覆冰涂层太阳光利用效率不足、涂层稳定性不够、难以适用于输电导线曲面以及除冰过程依赖外部电能或机械力等问题,提供一种用于输电导线的太阳光响应型光热超疏水防覆冰除冰涂层及其制备方法
1)本发明构建的Fe3O4-CuS@C三元光热复合颗粒,将Fe3O4、CuS和碳层的光吸收与光热转换能力相结合,可有效提高太阳光谱利用效率和局域光热转换能力。
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] This invention belongs to the field of photothermal anti-icing and de-icing materials technology, specifically relating to a solar-responsive photothermal superhydrophobic anti-icing and de-icing coating, its preparation method, and its application in power transmission lines. Background Technology
[0002] Icing is a common problem faced by power transmission lines, wind power equipment, transportation facilities, communication towers, and outdoor power equipment in cold and humid environments. For overhead transmission lines, the continuous deposition of supercooled water droplets, freezing rain, rime, or wet snow on the conductor surface easily forms ice layers, icicles, or uneven icing structures, thereby increasing the conductor load, altering the conductor's aerodynamic characteristics, and inducing safety accidents such as line galloping, line breakage, tower collapse, insulation flashover, and power outages. Traditional de-icing methods mainly include mechanical de-icing, electrothermal de-icing, chemical de-icing agent treatment, and manual inspection and removal. However, mechanical de-icing suffers from low efficiency, poor continuity, and high operational risks; electrothermal de-icing requires additional energy input and has high requirements for grid operation status, equipment tolerance, and energy regulation; chemical de-icing agents may cause environmental pollution and metal corrosion problems. Therefore, developing low-energy-consumption, sustainable anti-icing and de-icing coatings integrated with the conductor surface is of significant engineering importance.
[0003] Superhydrophobic surfaces, due to their high water contact angle, low droplet adhesion, and excellent self-cleaning properties, are considered an important technological approach for delaying icing and reducing water retention. By constructing micro / nano rough structures and low surface energy interfaces, water droplets can be in a Cassie-Baxter wetting state, thereby reducing the actual solid-liquid contact area and decreasing heat conduction between the droplet and the substrate, which is beneficial for delaying droplet icing. However, traditional superhydrophobic coatings may still undergo wetting state transitions under conditions of extreme cold, continuous condensation, frost, or supercooled water impact. Once water droplets or ice crystals enter the surface rough structure, the superhydrophobic interface may fail, and the already formed ice layer is difficult to actively remove through passive superhydrophobicity.
[0004] Photothermal materials can absorb sunlight and convert it into heat energy, providing a new approach for low-energy active de-icing. Combining photothermal conversion materials with superhydrophobic interfaces can achieve synergy between "passive anti-icing" and "active de-icing": before icing, the superhydrophobic surface reduces water retention and heat transfer; under illumination, the photothermal material absorbs sunlight and generates localized heat at the coating / ice interface, further delaying icing and promoting ice melting. However, existing photothermal superhydrophobic coatings still suffer from insufficient broad-spectrum absorption, single photothermal component, poor adaptability to curved wire surfaces, and insufficient low-temperature anti-icing and de-icing capabilities, as well as insufficient wear and weather resistance. In existing technologies, photothermal materials, low surface energy modification, and spray film formation are typically used to improve light absorption, reduce surface energy, or improve construction adaptability, respectively. However, how to simultaneously achieve stable adhesion, maintain multi-level roughness structure, solar photothermal conversion, low-temperature icing suppression, and rapid de-icing on the curved surface of stranded wires still requires further research. Summary of the Invention
[0005] The main objective of this invention is to address the problems of insufficient solar utilization efficiency, inadequate coating stability, difficulty in application to curved surfaces of power transmission lines, and reliance on external electrical energy or mechanical force in the de-icing process of existing photothermal superhydrophobic anti-icing coatings. This invention provides a solar-responsive photothermal superhydrophobic anti-icing and de-icing coating for power transmission lines and its preparation method.
[0006] To achieve the above objectives, the technical solution adopted by the present invention includes: A solar-responsive photothermal superhydrophobic anti-icing and de-icing coating comprises a resin base layer and a modified Fe3O4-CuS@C photothermal superhydrophobic top layer. The topcoat used to prepare the modified Fe3O4-CuS@C photothermal superhydrophobic top layer contains Fe3O4-CuS@C photothermal composite particle alcohol dispersion, alkaline solution and low surface energy silane.
[0007] Furthermore, the Fe3O4-CuS@C photothermal composite particles comprise Fe3O4-CuS composite particles and a C layer coating their surface; the Fe3O4-CuS composite particles comprise tightly coupled spherical Fe3O4 particles and plate-like CuS nanocrystals, wherein the particle size of Fe3O4 is 20~50 nm and the plate size of CuS is 50~120 nm; the C layer is amorphous carbon with a thickness of 10~20 nm.
[0008] Furthermore, the Fe3O4-CuS@C photothermal composite particles first generate CuS in situ on the Fe3O4 surface to obtain tightly coupled Fe3O4-CuS, and then coat the surface of the Fe3O4-CuS composite material with a layer of hydrothermal carbon through a hydrothermal reaction.
[0009] Furthermore, in the Fe3O4-CuS@C photothermal composite particles, the molar ratio of Cu atoms introduced by the copper source, Fe atoms introduced by Fe3O4, and C atoms is preferably 1~6:1~2:75~90.
[0010] In the above scheme, the concentration of Fe3O4-CuS@C photothermal composite particles in the alcohol dispersion of Fe3O4-CuS@C photothermal composite particles is (60~71) mg / mL.
[0011] Furthermore, the volume ratio of the alcohol dispersion, alkaline solution, and low surface energy silane in the Fe3O4-CuS@C photothermal composite particles is (14.8~18.6): (0.3~0.7): (3.8~4.9).
[0012] In the above scheme, the low surface energy silane can be selected from one or more of the following: silane coupling agent, hexamethyldisilazane (HMDS), polydimethylsiloxane (PDMS), octyltriethoxysilane (OTES), fluorosilane, alkylsilane, organosilicon resin, etc.
[0013] Preferably, the low surface energy silane comprises at least polydimethylsiloxane.
[0014] More preferably, the low surface energy silane includes hexamethyldisilazane and polydimethylsiloxane.
[0015] In the above scheme, the alkaline solution is an aqueous solution of NaOH or ammonia, wherein the concentration of NaOH is 0.9~1.9 mol / L and the concentration of ammonia is 24~30 wt%.
[0016] In the above scheme, the resin underlayer adopts a resin primer comprising resin and alcohol solvent, wherein the resin can be selected from one or more of epoxy resin, polyurethane resin, acrylic resin, polyamide resin, etc.
[0017] Furthermore, the alcohol solvent may be one or more of methanol, ethanol, isopropanol, etc.
[0018] The preparation method of the above-mentioned solar-responsive photothermal superhydrophobic anti-icing and de-icing coating includes the following steps: (1) Fe3O4 particles were dispersed in an aqueous system containing sulfur source and surface regulator, copper source was added, and the mixture was stirred to allow CuS to be deposited and grown on the surface of Fe3O4 particles in situ, thus obtaining Fe3O4-CuS composite particle dispersion. (2) Add carbon source and dispersant to the Fe3O4-CuS composite particle dispersion obtained in step (1) and carry out hydrothermal carbonization reaction to obtain Fe3O4-CuS@C photothermal composite particles; (3) Disperse the Fe3O4-CuS@C photothermal composite particles obtained in step (2) in an alcohol solvent to obtain an alcohol dispersion of Fe3O4-CuS@C photothermal composite particles. Then add an alkaline solution and a low surface energy silane and perform surface modification under stirring conditions to obtain a photothermal Fe3O4-CuS@C superhydrophobic dispersion (topcoat). (4) Spray a resin primer onto the substrate surface and cure it to form a resin primer coating; (5) Spray the photothermal Fe3O4-CuS@C superhydrophobic dispersion obtained in step (3) onto the surface of the resin base coating obtained in step (4), and cure it to obtain the solar responsive photothermal superhydrophobic anti-icing and de-icing coating.
[0019] In the above scheme, the copper source is one or more of cuprous chloride dihydrate, copper nitrate, etc.; the sulfur source is one or more of sodium sulfide nonahydrate, sulfur powder, etc.
[0020] In the above scheme, the molar ratio of Cu atoms introduced by the copper source to Fe atoms introduced by the Fe3O4 particles is 1~6:1~2.
[0021] In the above scheme, the surface regulator can be one or more of 3-mercaptopropionic acid, citric acid, etc.
[0022] In the above scheme, the molar ratio of the surface modifier to the S source is (0.5~1.5):(1.5~2.5). In the above scheme, the carbon source is one or more of glucose, sucrose, etc.
[0023] In the above scheme, the dispersant can be one or more of polyethylene glycol, polyvinylpyrrolidone, polyvinyl alcohol, polyacrylic acid, etc.
[0024] In the above technical solution, the mass ratio of the carbon source, dispersant and Fe3O4-CuS composite particles introduced in step (2) is (10~18): (0.2~1): (1~1.5).
[0025] In the above scheme, the resin in the resin primer preferably includes epoxy resin and polyamide resin; wherein, the mass ratio of epoxy resin to polyamide resin is (20~35):(18~27); and the mass ratio of epoxy resin to alcohol solvent is 20:(110~140).
[0026] In the above scheme, the stirring reaction time in step (1) is 2~8 h, and the reaction temperature is room temperature.
[0027] In the above scheme, the temperature of the hydrothermal carbonization reaction in step (2) is 120~220℃. o C, the hydrothermal reaction time is 4~10h.
[0028] In the above scheme, the stirring time for the surface modification in step (3) is 18~24 h, and the reaction temperature is room temperature.
[0029] Preferably, in step (3), alkali solution and hexamethyldisilazane are added first, and the mixture is stirred for 18-26 h; then polydimethylsiloxane is added, and the mixture is stirred for 3-6 h.
[0030] Furthermore, the stirring rate used in step (3) is 800~1000 rpm.
[0031] In the above scheme, the substrate can be a glass substrate or the surface of the wire, etc.
[0032] Preferably, in step (4), a resin primer is sprayed as a binder to improve the wear resistance and weather resistance of the coating, and the substrate coated with the primer is cured at a temperature of 40~80°C. o C, curing time 4~10 minutes. Then spray the superhydrophobic Fe3O4-CuS@C photothermal composite coating and dry for 12~24 hours to obtain the superhydrophobic Fe3O4-CuS@C photothermal anti-icing coating.
[0033] This invention also provides an application of the aforementioned solar-responsive photothermal superhydrophobic anti-icing and de-icing coating in power transmission lines, wherein the power transmission line is a stranded conductor with a diameter of 4-6 cm. The surface of the stranded conductor is not an ideal smooth cylindrical surface, but a complex curved surface composed of multiple helical strands. This special structure makes it easy for conventional coatings to have problems such as uneven thickness, accumulation in the gaps between the strands, or incomplete coverage during application. The resin primer coats the surface of the conductor and fills the gaps between the strands, ensuring uniform coverage of the topcoat.
[0034] The Fe3O4-CuS@C photothermal superhydrophobic coating obtained according to the above scheme has a broad spectrum of solar light absorption capability, with a solar light absorption rate as high as 95.36% and a water contact angle as high as 166.9°. o .
[0035] The principle of this invention is as follows: This invention is the first to employ Fe3O4, CuS, and a carbon layer to construct a ternary photothermal structure: the CuS component enhances visible and near-infrared light absorption, the Fe3O4 component provides additional light absorption and composite structural support, and the carbon layer enhances broadband solar light absorption and promotes localized heat generation; the resulting Fe3O4-CuS coupled material combines the light absorption capacity and good stability of Fe3O4 with the visible-near-infrared absorption capacity of CuS; in addition, the introduced CuS can promote the broadening of the ultraviolet-visible light response range of Fe3O4; the resulting Fe3O4-CuS composite particles exhibit a strong solar light absorption rate and can simultaneously enhance photothermal absorption performance, thereby promoting the improvement of the photothermal conversion efficiency of Fe3O4. Furthermore, by combining the hydrothermal coated carbon layer (not just a simple photothermal filler), it also serves as a structural guiding layer and a surface functionalization platform: further promoting particle aggregation and the formation of multi-level micro-nano rough structures, and providing modification sites for low surface energy organosilicon components (HMDS, PDMS, etc.), prompting the particle assembly layer to form a stable superhydrophobic Cassie state. The presence of the carbon layer can also further improve the acid and alkali resistance of the superhydrophobic material.
[0036] The resin primer acts as a bonding and buffering layer, improving the adhesion between the functional particle layer and the substrate surface, enabling the coating to form a film on both planar substrates and curved stranded wire surfaces.
[0037] In cold and humid environments, the multi-level micro-nano rough structure and low surface energy interface of the coating cause water droplets to form near-spherical shapes and easily roll off, effectively inhibiting water retention, continuous water film formation, and ice growth on the substrate surface. Under sunlight, the Fe3O4-CuS@C photothermal composite particles rapidly convert sunlight into heat energy, generating localized heating at the coating / water droplet or coating / ice interface, delaying water droplet freezing and promoting ice melting and shedding. This achieves a synergistic effect of passive superhydrophobic anti-icing and active solar-assisted de-icing.
[0038] Compared with the prior art, the present invention has the following beneficial effects: 1) The Fe3O4-CuS@C ternary photothermal composite particles constructed in this invention combine the light absorption and photothermal conversion capabilities of Fe3O4, CuS and carbon layers, which can effectively improve the utilization efficiency of solar spectrum and the local photothermal conversion capability.
[0039] 2) The carbon layer in this invention has dual functions of photothermal enhancement and interface construction (superhydrophobic surface micro-nano structure construction), which can promote the formation of multi-level rough structures and provide low surface energy modification sites, which is beneficial to constructing a stable superhydrophobic Cassie interface. The presence of the carbon layer can also improve the acid and alkali resistance of superhydrophobic materials.
[0040] 3) The present invention adopts a double-layer spraying structure combining resin primer and photothermal superhydrophobic topcoat, which can be applied to flat or curved substrates such as glass, metal and power transmission lines, and can also be used for anti-icing / de-icing protection of the surface of overhead power transmission lines.
[0041] 4) The coating of this invention has the properties of low water droplet adhesion, anti-fouling and self-cleaning, rapid photothermal heating, delayed icing, solar-assisted de-icing, and certain wear and weather resistance, which can reduce the reliance on electric heating or mechanical de-icing. Attached Figure Description
[0042] Figure 1 This is a transmission electron microscope (TEM) image of the Fe3O4-CuS composite material obtained in Example 1.
[0043] Figure 2 This is a transmission electron microscope (TEM) image of the Fe3O4-CuS@C photothermal composite material obtained in Example 1.
[0044] Figure 3 This is a high-resolution transmission electron microscope (HRTEM) image of the Fe3O4-CuS composite material obtained in Example 1.
[0045] Figure 4 The images show the XRD patterns of the Fe3O4-CuS@C photothermal composite powder and Fe3O4-CuS powder obtained in Example 1.
[0046] Figure 5 The image shows the morphology of the coating sample obtained in Example 1.
[0047] Figure 6 This is a photograph of the contact angle of the coating sample obtained in Example 1.
[0048] Figure 7 This is a scanning electron microscope (SEM) image of the superhydrophobic Fe3O4-CuS@C photothermal composite coating obtained in Example 1.
[0049] Figure 8 The infrared spectrum characterization of the superhydrophobic Fe3O4-CuS@C photothermal composite particles obtained in Example 1 is shown.
[0050] Figure 9 The image shows the UV-Vis-NIR diffuse reflectance spectrum absorption curve of the superhydrophobic Fe3O4-CuS@C photothermal composite coating obtained in Example 1.
[0051] Figure 10 The temperature rise of the superhydrophobic Fe3O4-CuS@C photothermal composite coating and the blank glass slide in Application Example 1 is shown.
[0052] Figure 11 For example 1, at various temperatures (-30°C) under dark conditions. o C, -20o C and -15 o C) The delayed freezing time of the superhydrophobic Fe3O4–CuS@C photothermal composite coating and the blank glass slide.
[0053] Figure 12 For example 1, under different solar radiation intensities and an ambient temperature of -30°C... o The delayed freezing time of the superhydrophobic Fe3O4-CuS@C photothermal composite coating and the superhydrophobic hydrothermal carbon coating under the condition of C.
[0054] Figure 13 The changes in contact angle and roll-off angle of the superhydrophobic Fe3O4-CuS@C photothermal composite coating described in Example 1 after ten freeze-thaw cycles are shown.
[0055] Figure 14 The wear resistance test was conducted on the contact angle and roll-off angle of the superhydrophobic Fe3O4-CuS@C photothermal composite coating described in Example 1.
[0056] Figure 15 The Fe3O4-CuS@C photothermal composite anti-icing coating and superhydrophobic SiO2 coating described in Example 1 were immersed in NaOH solution at pH = 13, and the change in the contact angle of the coating was observed.
[0057] Figure 16 The change in contact angle of the Fe3O4-CuS@C photothermal composite anti-icing coating described in Example 1 was measured when it was immersed in corrosive solutions with different pH values (H2SO4 solution with pH=1, NaCl solution with pH=7 and 3.5wt% and NaOH solution with pH=13).
[0058] Figure 17 This is an example of indoor delayed icing conditions for coated and uncoated wires as described in Example 2.
[0059] Figure 18 This is an example of outdoor de-icing conditions using coated and uncoated conductors as described in Example 2. Detailed Implementation
[0060] The present invention will be further described below with reference to the embodiments, but the scope of protection of the present invention is not limited to the following embodiments. Equivalent substitutions or conventional adjustments made by those skilled in the art to the types of raw materials, dosage ranges, spraying methods, curing conditions, substrate types, and application scenarios without departing from the concept of the present invention should all fall within the scope of protection of the present invention.
[0061] Example 1 A solar-responsive, photothermal superhydrophobic anti-icing and de-icing coating, the preparation method of which includes the following steps: 1) Preparation of Fe3O4-CuS photothermal composite particles Weigh 0.43 g CuCl2·2H2O (2.5 mmol), dissolve it in 62.5 mL of deionized water to prepare a 0.04 mol / L copper source solution. Separately, dissolve 1.20 g Na2S·9H2O (5 mmol) in 15.5 mL of deionized water, add 12.5 mL of 0.2 mol / L 3-mercaptopropionic acid solution to obtain a mixed solution containing a sulfur source and a coordination modifier.
[0062] 0.20 g of Fe3O4 nanoparticles and 0.025 g of CTAB were added to the mixed solution and ultrasonically dispersed for 30 min to obtain a uniform Fe3O4 dispersion system.
[0063] Under magnetic stirring, the above Fe3O4 dispersion system was added dropwise to a copper source solution, and the reaction was continued with stirring for 4 hours, allowing CuS to form in situ on the surface of Fe3O4 particles and forming Fe3O4-CuS composite particles. After the reaction was completed, the precipitate was separated by washing twice with a centrifuge (4000 rpm, 5 min), and then deionized water was added to disperse the precipitate evenly, resulting in a Fe3O4-CuS dispersion.
[0064] 2) Preparation of Fe3O4-CuS@C photothermal composite particles Add 6.0 g of glucose and 0.30 g of PVP to the Fe3O4-CuS dispersion obtained in step 1) (the content of Fe3O4-CuS composite particles is 0.44 g). Adjust the total volume to 60 mL with deionized water. After ultrasonic treatment for 30 min, transfer the resulting uniform dispersion to a polytetrafluoroethylene liner and then to a hydrothermal reactor. Incubate at 180 °C. o The hydrothermal reaction was carried out at C for 6 h. After the reaction was completed, the mixture was allowed to cool naturally to room temperature, and the solid product was collected, washed successively with deionized water and ethanol, and then heated at 80°C. o After drying at C for 4 h, Fe3O4-CuS@C photothermal composite particles were obtained by grinding.
[0065] In the obtained Fe3O4-CuS@C photothermal composite particles, the Fe3O4 and CuS components maintain their crystalline structure, while an amorphous carbonaceous coating layer forms on the outside. This carbonaceous layer enhances light absorption and thermal localization, while also promoting subsequent low surface energy modification and the formation of micro / nano rough structures.
[0066] 3) Low surface energy modification of Fe3O4-CuS@C photothermal composite particles Weigh 1.0 g of the Fe3O4-CuS@C photothermal composite particles obtained in step 2), disperse them in 15 mL of ethanol, and then add 0.30 mL of NaOH solution, 0.45 mL of KH550, and 4.0 mL of HMDS sequentially. The mixture is stirred at 1000 rpm for 24 h to allow the silane component to react with the particle surface and introduce low surface energy groups corresponding to HMDS. Subsequently, 0.22 g of PDMS (Dow Corning 184) is added, and stirring continues for 4 h to obtain the modified Fe3O4-CuS@C photothermal superhydrophobic dispersion.
[0067] 4) Preparation of photothermal superhydrophobic anti-icing and de-icing coating Weigh 6.0 g of epoxy resin and 4.8 g of polyamide resin, add them to 50 mL of ethanol, and stir under magnetic stirring for 2 h to obtain a resin primer. After cleaning and drying the substrate, spray the resin primer onto the substrate surface and then heat it at 70°C. o Pre-dry at C for 4 min to form a resin primer layer.
[0068] Subsequently, the modified Fe3O4-CuS@C photothermal superhydrophobic dispersion obtained in step 3) is sprayed onto the surface of the resin primer. A spray gun or air pen can be used for spraying, with a nozzle diameter of 1.0 mm, a spraying pressure of 2.0–2.5 bar, and a spraying distance of 15–20 cm. After spraying, drying is performed to obtain a solar-responsive photothermal superhydrophobic anti-icing and de-icing coating.
[0069] Figure 1 The image shows a transmission electron microscope (TEM) image of the Fe3O4-CuS composite material obtained in step 1) of this embodiment, in which nanosheet-like CuS and spherical Fe3O4 particles are tightly coupled. The particle size of Fe3O4 is 20-50 nm, and the particle size of CuS is 50-120 nm.
[0070] Figure 2 The image shown is a transmission electron microscope (TEM) image of the Fe3O4-CuS@C photothermal composite material obtained in step 2). It can be seen that the carbon layer forms a good coating growth on the Fe3O4-CuS surface.
[0071] Figure 3 The image shown is a high-resolution transmission electron microscope (HRTEM) image of the Fe3O4-CuS composite material obtained in this embodiment. It shows that there is a clear, continuous and impurity-free interface between Fe3O4 and CuS, and the two are tightly bonded, indicating that Fe3O4-CuS composite particles have been formed.
[0072] Figure 4 The images show the XRD patterns of the Fe3O4-CuS@C photothermal composite powder and the Fe3O4-CuS powder obtained in this embodiment, where 2θ is 15-28.o The broad peak can be attributed to the formation of amorphous carbon. This indicates the successful combination of Fe3O4-CuS and hydrothermal carbon.
[0073] Figure 5 , 6 The images show the morphology and contact angle of the coating sample obtained in this embodiment. The coating exhibits good anti-wetting and low-adhesion properties against various aqueous liquids such as water, beverages, and dye solutions. The measured water contact angle is 166.9°. o The resulting coated samples exhibited excellent superhydrophobic properties.
[0074] Figure 7 The image shows a scanning electron microscope (SEM) image of the superhydrophobic Fe3O4-CuS@C photothermal composite coating obtained in this embodiment. Carbon forms a good coating growth on the Fe3O4-CuS surface, constructing a micro-nano hierarchical structure. The resulting coating sample has good superhydrophobic properties.
[0075] Figure 8 The infrared spectrum characterization of the superhydrophobic Fe3O4-CuS@C photothermal composite particles obtained in this embodiment confirms the successful introduction of hydrophobic siloxanes, indicating that HMDS / PDMS modification introduces methyl-terminated siloxane groups into the surface of the photothermal particles, thereby reducing the surface energy and providing a chemical basis for superhydrophobicity.
[0076] Figure 9 The image shows the UV-Vis-NIR diffuse reflectance spectrum absorption curve of the superhydrophobic Fe3O4-CuS@C photothermal composite coating obtained in this embodiment. The results show that the Fe3O4-CuS@C photothermal superhydrophobic coating has a broad spectrum of solar light absorption capability, with a solar light absorption rate of up to 95.36%.
[0077] Example 2 A solar-responsive, photothermal superhydrophobic anti-icing and de-icing coating, the preparation method of which includes the following steps: 1) Preparation of Fe3O4-CuS photothermal composite particles Weigh 0.60 g of CuSO4·5H2O (2.4 mmol) and dissolve it in 60 mL of deionized water to prepare a 0.04 mol / L copper source solution. Separately, dissolve 1.20 g of Na2S·9H2O (5 mmol) in 15.5 mL of deionized water, add 12.5 mL of 0.2 mol / L 3-mercaptopropionic acid solution, and obtain a mixed solution containing a sulfur source and a coordination modifier. Add 0.20 g of Fe3O4 nanoparticles and ultrasonically disperse for 30 min to obtain a mixed dispersion containing a sulfur source, dispersant, and Fe3O4.
[0078] Under magnetic stirring, the above-mentioned mixed dispersion was slowly added dropwise to the copper source solution, and the reaction was carried out at room temperature for 4 h to allow CuS to grow in situ on the surface of Fe3O4 particles. After the reaction was completed, the precipitate was collected by centrifugation, washed three times alternately with deionized water and anhydrous ethanol, and then discharged at 80 °C. o After drying at C for 4 h, Fe3O4-CuS composite particles were obtained by grinding.
[0079] 2) Preparation of Fe3O4-CuS@C photothermal composite particles Weigh 0.50 g of the Fe3O4-CuS composite particles obtained in step 1), disperse them in 50 mL of deionized water, add 8.0 g of sucrose and 0.20 g of polyethylene glycol (PEG-4000), and ultrasonically disperse for 30 min. Transfer the resulting dispersion to a 100 mL polytetrafluoroethylene-lined hydrothermal reactor and heat at 190 °C. o The hydrothermal reaction was carried out at C for 8 h. After natural cooling to room temperature, the product was washed sequentially with deionized water and ethanol by centrifugation (4000 rpm, 5 min), and then centrifuged at 80 °C. o After drying at C for 6 h, Fe3O4-CuS@C photothermal composite particles were obtained by grinding.
[0080] 3) Low surface energy modification of Fe3O4-CuS@C photothermal composite particles Weigh 1.0 g of the Fe3O4-CuS@C photothermal composite particles obtained in step 2), disperse them in 20 mL of isopropanol, add 0.50 mL of ammonia (25 wt%) and 2.0 mL of octyltriethoxysilane (OTES), and react with magnetic stirring at room temperature for 24 h. Then add 0.22 g of PDMS (the same PDMS system used in Example 1), and continue stirring for 4 h to obtain the modified Fe3O4-CuS@C photothermal superhydrophobic dispersion.
[0081] 4) Preparation of photothermal superhydrophobic anti-icing and de-icing coating Weigh 6.0 g of epoxy resin and 4.8 g of polyamide resin (same as in Example 1), add them to 50 mL of ethanol, and stir under magnetic stirring for 2 h to obtain a resin primer. After cleaning and drying the substrate, spray the resin primer onto the substrate surface and then heat it at 70°C. o Pre-dry at C for 4 min to form a resin primer layer. Then, spray the modified Fe3O4-CuS@C photothermal superhydrophobic dispersion obtained in step 3 onto the surface of the resin primer layer. Spraying can be done using a spray gun or air pen with a nozzle diameter of 1.0 mm, a spraying pressure of 2.0–2.5 bar, and a spraying distance of 15–20 cm. After spraying, dry to obtain a solar-responsive photothermal superhydrophobic anti-icing and de-icing coating.
[0082] Application Example 1 A superhydrophobic Fe3O4-CuS@C composite photothermal coating was prepared according to the preparation method described in Example 1 and applied to the anti-icing field. A glass substrate was selected as the base, and after removing surface oil and dust, it was dried. The same resin primer as in Example 1 was sprayed onto the surface. After the primer layer pre-dryed, the modified Fe3O4-CuS@C photothermal superhydrophobic dispersion obtained in Example 1 was uniformly sprayed onto the surface to obtain a solar-responsive photothermal superhydrophobic anti-icing and de-icing coating. It was then applied at -30°C. o C. The anti-icing effect of the obtained Fe3O4-CuS@C photothermal composite anti-icing coating was investigated by comparing it with the glass slide coating sample coated only with superhydrophobic hydrothermal carbon coating under different light intensities (and compared with the traditional superhydrophobic SiO2 coating).
[0083] The specific steps for preparing the superhydrophobic hydrothermal carbon coating are as follows: (1) Add 6 g of anhydrous glucose to 60 ml of deionized water, transfer the resulting solution to a polytetrafluoroethylene liner, and then transfer it to a hydrothermal reactor. Heat the reactor at 180°C. o The hydrothermal reaction was carried out at C for 6 h. After the reaction was completed, the mixture was allowed to cool naturally to room temperature, and the solid product was collected, washed successively with deionized water and ethanol, and then heated at 80°C. o Drying at C for 4 h and grinding to obtain hydrothermal carbon powder; (2) Modification of hydrothermal carbon powder was completed with reference to Example 1; (3) The superhydrophobic hydrothermal carbon coating was prepared according to Example 1; The specific steps for preparing the superhydrophobic SiO2 coating are as follows: (1) Add 1.5 mL of NaOH solution (1.8 mol / L) and 5 mL of tetraethyl orthosilicate to 25 mL of ethanol and stir for 24 h; (2) Add 5.0 mL of hexamethyldisilazane (HMDS) to the solution system in step 1) and continue stirring for 12 h to obtain a superhydrophobic SiO2 photothermal composite coating. (3) Spray the coating obtained in step 2) onto the substrate surface and dry it to obtain a superhydrophobic SiO2 coating.
[0084] The specific performance testing steps for the obtained superhydrophobic hydrothermal carbon coating and superhydrophobic SiO2 coating are as follows: (a) Comparison of the delayed freezing time of Fe3O4-CuS@C photothermal composite anti-icing coating and blank glass substrate under no light and different temperatures: The two glass slides were placed on a condensation stage at the same ambient temperature. When the surface temperature of the glass slides stabilized to the same ambient temperature, an equal amount (50 µL) of methylene blue dye solution (50 mg / L) was added, and the complete freezing time of the droplets was recorded. (b) Compare the delayed freezing time of Fe3O4-CuS@C photothermal composite anti-icing coating and superhydrophobic hydrothermal carbon coating at the same temperature and different light intensities, using the same method as above.
[0085] (c) Testing the changes in contact angle and roll-off angle of the Fe3O4-CuS@C photothermal composite anti-icing coating during freeze-thaw cycles: A glass slide coated with the Fe3O4-CuS@C coating was placed at -15°C. o On the condensation stage of C, 50 µL of MB liquid (50 mg / L) was dropped onto the coating surface without illumination. The time for the water droplet to completely freeze was recorded and an optical photograph was taken. After the water droplet had completely frozen, the temperature of the condensation stage was kept constant while the xenon lamp was turned on to apply illumination, and the melting process of the ice droplet was recorded in the same manner.
[0086] (d) Test of the wear resistance of Fe3O4-CuS@C photothermal composite anti-icing coating: A glass slide with the anti-icing coating measuring 10 cm × 10 cm × 0.5 mm was subjected to a constant slow speed (approximately 1 cm / s) under a load of 1000 g. -1 The sample is moved across sandpaper (800 grit) in a 10cm back-and-forth motion, with 20cm marking one wear cycle. After every 50 wear cycles, the changes in the contact angle and roll-off angle of the sample are measured.
[0087] (e) Testing the chemical stability of the Fe3O4-CuS@C photothermal composite anti-icing coating and the superhydrophobic SiO2 coating: The Fe3O4-CuS@C photothermal composite anti-icing coating and the superhydrophobic SiO2 coating were immersed in corrosive solutions with different pH values (H2SO4 solution with pH=1, NaCl solution with pH=7 and 3.5 wt% and NaOH solution with pH=13) to evaluate the chemical corrosion resistance of the coatings. The samples were taken out every 24 h, slowly rinsed with distilled water and dried, and the water contact angle of each coating was tested.
[0088] Figure 10 To simulate sunlight (light intensity of 100 mW / cm²) using a xenon lamp light source (model CEL-S500-T5). 2 Simultaneously, the superhydrophobic Fe3O4-CuS@C photothermal composite coating and a blank glass slide were irradiated, and temperature changes were recorded in real time using thermocouples to test the surface temperature rise. Figure 8 It can be seen that under 1 solar intensity, the surface temperature of the Fe3O4-CuS@C composite coating increases from 23.1°C to 120 seconds. o C rose to 55.9 o C rose by 32.8%. o C; while the surface temperature of the blank glass slide only increased from 23.1°C. o C rose to 31.3 oC, the increase was only 8.2. o The superhydrophobic Fe3O4-CuS@C photothermal composite coating reached a relatively high stable temperature under continuous illumination. After the illumination was turned off, the coating temperature gradually decreased, showing a reversible photothermal response.
[0089] Figure 11 For each temperature (-30) under dark conditions o C, -20 o C and -15 o C) The delayed freezing time of the superhydrophobic Fe3O4–CuS@C photothermal composite coating and the blank glass slide described in this application example. As shown in the figure, the Fe3O4-CuS@C photothermal superhydrophobic coating can significantly delay water droplet freezing due to its low adhesion and air insulation layer.
[0090] Figure 12 To simulate different solar radiation intensities and an ambient temperature of -30°C o Under C conditions, the delayed freezing time of the superhydrophobic Fe3O4-CuS@C photothermal composite coating and the superhydrophobic hydrothermal carbon coating described in this application example is further extended by the photothermal effect of the coating at 1 solar intensity. Typically, at -30°C... o Under C conditions, the freezing time of water droplets in the dark is approximately 234 s, while under 1 ray of sunlight, the freezing time can be extended to 1314 s. The Fe3O4-CuS@C superhydrophobic coating effectively suppresses water droplet freezing behavior and delays the freezing time. Figure 13 This shows the changes in contact angle and roll-off angle of the superhydrophobic Fe3O4-CuS@C photothermal composite coating described in this application example after ten freeze-thaw cycles. After ten freeze-thaw cycles, the water contact angle of the coating decreased slightly, and the roll-off angle increased slightly, but it still maintained its superhydrophobicity.
[0091] Figure 14 The wear resistance test was conducted on the superhydrophobic Fe3O4-CuS@C photothermal composite coating described in this application example to measure the changes in contact angle and roll-off angle.
[0092] Figure 15 The change in the contact angle of the Fe3O4-CuS@C photothermal composite anti-icing coating and the superhydrophobic SiO2 coating described in this application example is observed when they are immersed in a NaOH solution with pH = 13.
[0093] Figure 16 The change in contact angle of the Fe3O4-CuS@C photothermal composite anti-icing coating described in this application example is shown when it is immersed in corrosive solutions with different pH values (H2SO4 solution with pH=1, NaCl solution with pH=7 and 3.5wt% and NaOH solution with pH=13).
[0094] Application Example 2 According to the preparation method described in Example 1, a superhydrophobic Fe3O4-CuS@C composite photothermal coating was prepared and applied to the anti-icing field. Overhead transmission lines or stranded metal conductors (4-6 cm in diameter) were selected as the substrate, and surface oil and dust were removed and the conductors were dried. The same resin primer as in Example 1 was sprayed onto the conductor surface, covering the outer surface of the conductor and the uneven structure of the stranded conductors. After the primer was pre-dried, the modified Fe3O4-CuS@C photothermal superhydrophobic dispersion obtained in Example 1 was uniformly sprayed onto the conductor surface, resulting in a transmission line coated with a solar-responsive photothermal superhydrophobic anti-icing and de-icing coating.
[0095] Because the spraying method can adapt to the curved surface and stranded structure of the conductor, the resulting functional layer can form a continuous photothermal superhydrophobic interface on the conductor surface. When supercooled water droplets or freezing rain come into contact with the conductor surface, the water droplets do not easily spread or remain; under natural light or simulated sunlight, the coating can absorb light energy and generate local heat, thereby delaying the freezing of water droplets and promoting the melting of ice.
[0096] The uncoated wire and the coated wire obtained in Application Example 2 were placed in a low-temperature environment (-5). o C ~-10 o C) Pre-cooling was performed, followed by periodic spraying of supercooled water to simulate the impact of water droplets and ice accumulation in a cold and humid environment. After freezing for 3 hours, the anti-icing effect of the two types of wires was tested. The uncoated and coated wires, after being iced, were then transferred to outdoor natural light conditions (cloudy day, 24 hours). o C) Conduct a de-icing test.
[0097] Figure 17 The indoor delayed icing conditions of the coated and uncoated wires described in this application example are shown. The results indicate that water retention and continuous ice droplets and icicles easily form on the surface of the uncoated wire; in contrast, only a small amount of discontinuous ice residue appears on the surface of the wire coated with the Fe3O4-CuS@C photothermal superhydrophobic coating, which can significantly inhibit water retention, ice accumulation and long icicle formation.
[0098] Figure 18 The images show the outdoor de-icing conditions of the coated and uncoated conductors described in this application example. Under natural light, the coated conductor exhibits faster interface de-icing and ice layer detachment, with most visible ice removed within approximately 5 minutes and 39 seconds; while the uncoated conductor still retains a noticeable ice structure after 11 minutes and 41 seconds. These results demonstrate that the coating of this invention can achieve natural light-assisted de-icing without the application of electric heating or mechanical force.
[0099] Comparative Example 1 A Fe3O4-CuS-C photothermal composite dispersion is prepared by the following steps: 1) Add 60 ml of 0.56 mol / L glucose solution and 0.30 g of PVP to the liner of a 100 ml reactor, and heat at 180 °C. o The hydrothermal reaction was carried out at C for 6 h. The solid product was collected and dried (at 80°C). o Hydrothermal C particles were obtained by grinding C, 4h.
[0100] 2) 0.50 g each of Fe3O4-CuS composite particles (prepared using the same method as in Example 1) and hydrothermal C particles were dispersed in 15 mL of ethanol. Then, 0.30 mL of NaOH solution, 0.45 mL of KH550, and 4.0 mL of HMDS were added sequentially. The mixture was stirred at 1000 rpm for 24 h to allow the silane component to react with the particle surface and introduce low surface energy groups. Subsequently, 0.22 g of PDMS (same as in Example 1) was added, and stirring was continued for 4 h to obtain a modified Fe3O4-CuS-C photothermal superhydrophobic dispersion.
[0101] The obtained superhydrophobic Fe3O4-CuS-C photothermal composite material was used to prepare a superhydrophobic Fe3O4-CuS-C photothermal coating. The specific steps included: 1) Under stirring conditions, 6.0 g of epoxy resin and 4.8 g of polyamide resin were added to 50 ml of ethanol in sequence and stirred for 2-4 h to obtain a resin primer; 2) On the surface of a glass substrate (7.5×2.5 cm), the resin primer obtained in step 1) was first sprayed as a binder to improve the wear resistance and weather resistance of the coating. After the primer was cured, the hydrophobic Fe3O4-CuS-C photothermal composite coating was sprayed and dried to obtain a superhydrophobic Fe3O4-CuS-C photothermal anti-icing coating.
[0102] Comparative Example 2 A Fe3O4-CuS@C photothermal composite dispersion is prepared using a method largely the same as in Example 1, with the only difference being: In step 3): Weigh 1.0 g of the obtained Fe3O4-CuS@C photothermal composite particles, disperse them in 15 mL of ethanol, and add 0.30 mL of NaOH solution, 0.45 mL of KH550 and 4.0 mL of HMDS in sequence. React for 24 h under stirring at 1000 rpm to allow the silane component to react with the particle surface and introduce the low surface energy groups corresponding to HMDS, thus obtaining the modified Fe3O4-CuS@C photothermal superhydrophobic dispersion.
[0103] The obtained superhydrophobic Fe3O4-CuS@C photothermal composite material was used to prepare a superhydrophobic Fe3O4-CuS@C photothermal coating. The specific steps included: 1) Under stirring conditions, 6.0 g of epoxy resin and 4.8 g of polyamide resin were added sequentially to 50 ml of alcohol solvent (ethanol, etc.), and stirred for 2-4 hours to obtain a resin primer; 2) On the surface of a glass substrate (7.5×2.5 cm), the resin primer obtained in step 1) was first sprayed as a binder to improve the wear resistance and weather resistance of the coating. After the primer was cured, the hydrophobic Fe3O4-CuS@C photothermal composite coating was sprayed and dried to obtain the superhydrophobic Fe3O4-CuS@C photothermal anti-icing coating.
[0104] Comparative Example 3 A Fe3O4-CuS@SiO2 photothermal composite dispersion is prepared by the following steps: 1) Add 1.5 mL of NaOH solution (1.8 mol / L), 2.3 mL of KH550 and 5 mL of tetraethyl orthosilicate sequentially to the Fe3O4-CuS dispersion (preparation method is the same as in Example 1), and hydrolyze for 24 h under stirring to obtain a superhydrophilic Fe3O4-CuS@SiO2 photothermal composite dispersion; 2) Add 4.0 mL of hexamethyldisilazane (HMDS) to the solution system in step 2) and continue stirring for 24 h to obtain a superhydrophobic Fe3O4-CuS@SiO2 photothermal composite dispersion.
[0105] The obtained superhydrophobic Fe3O4-CuS@SiO2 photothermal composite material was used to prepare a superhydrophobic Fe3O4-CuS@SiO2 photothermal coating. The specific steps included: 1) Under stirring conditions, 6.0 g of epoxy resin and 4.8 g of polyamide resin were added sequentially to 50 ml of alcohol solvent (ethanol, etc.), and stirred for 2-4 hours to obtain a resin primer; 2) On the surface of a glass substrate (7.5×2.5 cm), the resin primer obtained in step 1) was first sprayed as a binder to improve the wear resistance and weather resistance of the coating. After the primer was cured, the hydrophobic Fe3O4-CuS@SiO2 photothermal composite coating was sprayed and dried to obtain the superhydrophobic Fe3O4-CuS@SiO2 photothermal anti-icing coating.
[0106] Comparative Example 4 A Fe3O4-CuS@C photothermal composite dispersion is prepared using a method largely the same as in the examples, with the only difference being: In step 1), the preparation method of Fe3O4-CuS photothermal composite particles includes the following steps: Weigh 0.43 g CuCl2·2H2O (2.5 mmol), dissolve it in 62.5 mL of deionized water to prepare a 0.04 mol / L copper source solution. Separately, dissolve 1.20 g Na2S·9H2O (5 mmol) in 15.5 mL of deionized water to obtain a sulfur source solution.
[0107] 0.20 g of Fe3O4 nanoparticles and 0.025 g of CTAB were added to the sulfur source solution and ultrasonically dispersed for 30 min to obtain a uniform Fe3O4 dispersion system.
[0108] Under magnetic stirring, the above Fe3O4 dispersion system was added dropwise to the copper source solution, and the reaction was continued with stirring for 4 hours. After the reaction was completed, the precipitate was separated by washing twice with a centrifuge (4000 rpm, 5 min), and then deionized water was added to disperse the precipitate evenly to obtain Fe3O4-CuS dispersion.
[0109] The obtained superhydrophobic Fe3O4-CuS@C photothermal composite material was used to prepare a superhydrophobic Fe3O4-CuS@C photothermal coating. The specific steps included: 1) Under stirring conditions, 6.0 g of epoxy resin and 4.8 g of polyamide resin were added sequentially to 50 ml of alcohol solvent (ethanol, etc.), and stirred for 2-4 hours to obtain a resin primer; 2) On the surface of a glass substrate (7.5×2.5 cm), the resin primer obtained in step 1) was first sprayed as a binder to improve the wear resistance and weather resistance of the coating. After the primer was cured, the hydrophobic Fe3O4-CuS@C photothermal composite coating was sprayed and dried to obtain the superhydrophobic Fe3O4-CuS@C photothermal anti-icing coating.
[0110] The performance test results of the photothermal evaporators and photothermal anti-icing coatings prepared in Example 1 and Comparative Examples 1-4 are shown in Table 1.
[0111] Table 1
[0112] This invention is not limited to the embodiments described above. For those skilled in the art, adjustments or substitutions can be made to the Fe3O4 particle size, CuS / Fe3O4 ratio, carbon source type, hydrothermal carbonization conditions, type of low surface energy modifier, resin primer type, spraying method, curing regime, and application substrate without departing from the principles and essence of this invention. All such adjustments or substitutions should be considered to fall within the protection scope of this invention.
Claims
1. A solar-responsive, photothermal superhydrophobic anti-icing and de-icing coating, characterized in that, It includes a resin base layer and a modified Fe3O4-CuS@C photothermal superhydrophobic top layer. The topcoat used to prepare the modified Fe3O4-CuS@C photothermal superhydrophobic top layer contains Fe3O4-CuS@C photothermal composite particle alcohol dispersion, alkaline solution and low surface energy silane.
2. The solar-responsive photothermal superhydrophobic anti-icing and de-icing coating according to claim 1, characterized in that, The Fe3O4-CuS@C photothermal composite particles comprise Fe3O4-CuS composite particles and a C layer coating their surface. The Fe3O4-CuS composite particles consist of tightly coupled spherical Fe3O4 particles and plate-like CuS nanocrystals, wherein the particle size of Fe3O4 is 20-50 nm and the size of CuS plate-like particles is 50-120 nm. The C layer is amorphous carbon with a thickness of 10-20 nm.
3. The solar-responsive photothermal superhydrophobic anti-icing and de-icing coating according to claim 1, characterized in that, In the Fe3O4-CuS@C photothermal composite particles, the molar ratio of Cu atoms introduced by the copper source, Fe atoms introduced by Fe3O4, and C atoms is 1~6:1~2:75~90.
4. The solar-responsive photothermal superhydrophobic anti-icing and de-icing coating according to claim 1, characterized in that, In the topcoat, the concentration of Fe3O4-CuS@C photothermal composite particle alcohol dispersion is (60~71) mg / mL; the volume ratio of Fe3O4-CuS@C photothermal composite particle alcohol dispersion, alkaline solution, and low surface energy silane is (14.8~18.6): (0.3~0.7): (3.8~4.9).
5. The solar-responsive photothermal superhydrophobic anti-icing and de-icing coating according to claim 1, characterized in that, The low surface energy silane is one or more of the following: silane coupling agent, hexamethyldisilazane, polydimethylsiloxane, octyltriethoxysilane, fluorosilane, alkylsilane, and organosilicon resin.
6. The solar-responsive photothermal superhydrophobic anti-icing and de-icing coating according to claim 1, characterized in that, The resin underlayer is a resin primer comprising resin and alcohol solvent; wherein the resin is one or more of epoxy resin, polyurethane resin, acrylic resin, and polyamide resin; and the alcohol solvent is one or more of methanol, ethanol, and isopropanol.
7. The method for preparing the solar-responsive photothermal superhydrophobic anti-icing and de-icing coating according to any one of claims 1 to 6, characterized in that, Includes the following steps: (1) Fe3O4 particles were dispersed in an aqueous system containing sulfur source and surface regulator, copper source was added, and the mixture was stirred to allow CuS to be deposited and grown on the surface of Fe3O4 particles in situ, thus obtaining Fe3O4-CuS composite particle dispersion. (2) Add carbon source and dispersant to the Fe3O4-CuS composite particle dispersion obtained in step (1) and carry out hydrothermal carbonization reaction to obtain Fe3O4-CuS@C photothermal composite particles; (3) Disperse the Fe3O4-CuS@C photothermal composite particles obtained in step (2) in an alcohol solvent to obtain an alcohol dispersion of Fe3O4-CuS@C photothermal composite particles, then add an alkaline solution and a low surface energy silane to perform surface modification, and stir to obtain a photothermal Fe3O4-CuS@C superhydrophobic dispersion. (4) Spray a resin primer onto the substrate surface and cure it to form a resin primer coating; (5) Spray the photothermal Fe3O4-CuS@C superhydrophobic dispersion obtained in step (3) onto the surface of the resin primer coating obtained in step (4), and cure it to obtain the solar-responsive photothermal superhydrophobic anti-icing and de-icing coating.
8. The preparation method according to claim 1, characterized in that, The copper source is one or more of cuprous chloride dihydrate and copper nitrate; the sulfur source is one or more of sodium sulfide nonahydrate and sulfur powder; and the surface regulator is one or more of 3-mercaptopropionic acid and citric acid.
9. The preparation method according to claim 1, characterized in that, The molar ratio of Cu atoms introduced by the copper source to Fe atoms introduced by the Fe3O4 particles is 1~6:1~2; the molar ratio of the surface modifier to the S source is (0.5~1.5):(1.5~2.5).
10. The application of the solar-responsive photothermal superhydrophobic anti-icing and de-icing coating according to any one of claims 1 to 9.
